2008
DOI: 10.1159/000167840
|View full text |Cite
|
Sign up to set email alerts
|

Transition Zone Index and Bothersomeness of Voiding Symptoms as Predictors of Early Unfavorable Outcomes after Transurethral Resection of Prostate

Abstract: Introduction: The objective of this study was to establish the influence of preoperative parameters on unfavorable outcomes after transurethral resection of the prostate. Patients and Methods: In a prospective study, 90 patients underwent transurethral resection of the prostate. The standardized protocol was used to investigate parameters, preoperatively and after 6 months. The baseline values were analyzed with respect to the probability of predicting the effectiveness of the outcome. Results: All preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
5
2
Order By: Relevance
“…Additionally, to a certain extent, although some preoperative factors are related to surgical outcomes, such as P ves , P det Q max , P abd , BOOI, IPSS-t, QoL, and Q max , they are signi cantly less effective than MBOOI. Particularly, contrary to the ndings of the previous study, an additional nding is that a signi cant correlation between TZI and surgical e cacy was not observed [24].…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, to a certain extent, although some preoperative factors are related to surgical outcomes, such as P ves , P det Q max , P abd , BOOI, IPSS-t, QoL, and Q max , they are signi cantly less effective than MBOOI. Particularly, contrary to the ndings of the previous study, an additional nding is that a signi cant correlation between TZI and surgical e cacy was not observed [24].…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, to a certain extent, although some preoperative factors are related to surgical outcomes, such as P ves , P det Q max , P abd , BOOI, IPSS-t, QoL, and Q max , they are significantly less effective than MBOOI. Particularly, contrary to the findings of the previous study, an additional finding is that a significant correlation between TZI and surgical efficacy was not observed [ 26 ]. In addition, related studies have shown that the surgical effect of TURP is similar to that of green-light laser photo-selective vaporization of the prostate (PVP) and holmium laser enucleation of the prostate (HoLEP), and the PVP and HoLEP were not significantly better than the former [ 27 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Wang et al [19] analyzed 116 BPH patients and found that TZI and TZV were both positively correlated with BOOI and IPSS. Milonas et al [20] reported that lower TZI was an independent predictor of ineffective surgical outcome. In the present study, we found significant correlations in surgical patients between both TZI and IPP with parameters reflecting the level of BOO, such as Qmax, PdetQmax, and BOOI.…”
Section: Discussionmentioning
confidence: 99%